Absence of extraocular muscle pathology in Duchenne's muscular dystrophy: role for calcium homeostasis in extraocular muscle sparing (The Rockefeller University Press, 1995)
Duchenne muscular dystrophy (DMD) is characterized by clinical weakness and progressive necrosis of striated muscle as a consequence of dystrophin deficiency. While all skeletal muscle groups are thought to be affected, enigmatically, the extraocular muscles (EOM) appear clinically unaffected. Here we show that dystrophin deficiency does not result in myonecrosis or pathologically elevated levels of intracellular calcium ([Ca2+]i) in EOM. At variance with a previous report, we find no evidence for dystrophin-related protein/utrophin up- regulation in EOM. In vitro experiments demonstrate that extraocular muscles are inherently more resistant to necrosis caused by pharmacologically elevated [Ca2+]i levels when compared with pectoral musculature. We believe that EOM are spared in DMD because of their intrinsic ability to maintain calcium homeostasis better than other striated muscle groups. Our results indicate that modulating levels of [Ca2+]i in muscle may be of potential therapeutic use in DMD.